2004
DOI: 10.1542/peds.113.3.e225
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Physical Fitness in Children With Asthma

Abstract: ABSTRACT. Rationale. This study was designed to examine the relationships among weight, asthma severity, physical activity, and aerobic fitness in children with asthma.Subjects and Methods. Sixty-four asthmatic children 8 to 12 years old (53% female) were assessed while attending a summer asthma camp. Measures included height and weight, spirometry, histamine bronchial provocation challenge, maximal aerobic power, and questionnaires to quantify habitual activity, perceived activity limitations due to asthma, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
112
3
13

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(147 citation statements)
references
References 44 publications
19
112
3
13
Order By: Relevance
“…36 Additionally, studies in children with asthma have found them to be less physically fit than non-asthmatics, which could not be accounted for by their lung disease. 37 Over the long term, a lack of physical fitness could pre-dispose one to weight gain. Unfortunately, detailed information on asthma treatment was not available, and the level of physical activity was based on data from interviews in 1981 and 1986, making it impossible to test the relationship between asthma and physical activity over time.…”
Section: Discussionmentioning
confidence: 99%
“…36 Additionally, studies in children with asthma have found them to be less physically fit than non-asthmatics, which could not be accounted for by their lung disease. 37 Over the long term, a lack of physical fitness could pre-dispose one to weight gain. Unfortunately, detailed information on asthma treatment was not available, and the level of physical activity was based on data from interviews in 1981 and 1986, making it impossible to test the relationship between asthma and physical activity over time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, van Gent et al (10) did not found lower level of VPA based on both self-reports and objective recordings, and neither did Nystad (11) at any level of exercise frequency or exercise hours a week in asthma based on self-reports. Even though asthma control and severity are associated with level of PA (1,6,7), and that increased intensity and exercise load is associated with bronchoconstriction (12), there is also evidence that psychosocial and socio-demographical factors and knowledge/competence are important for level of physical activity in children and adolescents with asthma (1,(13)(14)(15)(16)(17)(18). Parents observing shortness of breath in their child may lead them to restrain their children from exertion (14), with subsequent increasing fear of breathlessness followed by personal or parental restrictions (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…(1) Asthma patients, due to the characteristics of the disease, suffer from increased airway resistance, as well as air trapping and lung hyperinflation, which lead to changes in the thoraco-abdominal mechanics and inspiratory muscle impairment. (2)(3)(4) Various respiratory therapy programs for patients with asthma, using inspiratory muscle training (IMT) or breathing exercises, have been studied as a complement to pharmacological treatment.…”
Section: Introductionmentioning
confidence: 99%